Nonlinear static and dynamic analysis of mulltilayer nanocomposite structures in solar cell - Vũ, Minh Anh (2020)
This thesis focuses on the study of the mechanical behavior of Solar Cell (SC). As we know, SC is a sustainable solution for energy supply and greenhouse gas reduction. Therefore, SC is currently hot topic that attracted a lot of interest from scientists worldwide. Currently, there are many research about SC such as Replace component materials in OS or how to improve SC performance ... However, there is very little research on mechanical properties, mechanical behavior of SC. Therefore, this thesis will focus on investigation of mechanical behavior of SC. SC are made by 5 layers under mechanical load. Besides, SC are supported by elastic foundations: winker foundation and Pasternak foundation. In details, nonlinear static and dynamic analysis of multilayer nanocomposite structure in solar cell will be investigated. By using classical plate theory, Glarkin method along with Runge - Kutta method, the effect of geometrical parameter, elastic foundation, load, and imperfection on the nonlinear static and dynamic analysis of multilayer nanocomposite structure in solar cell will be described in detail. Besides, some numerical results as critical buckling load and natural frequency also will be shown.